The Education System in West Sumatra from the 14th to the 19th Century as a Breeding Ground for National Movement Figures - Yusuf Budi Prasetya Santosa; Aksilas Dasfordate; Ponco Setiyonugroho (Criksetra: Jurnal Pendidikan Sejarah, 2025)
Every society in Indonesia has its own education pattern. The people of West Sumatra are no exception. Education in West Sumatra has been going on for a long time, since pre-Islamic times in the 14th century, until the influence of the Dutch in education in the 19th century. This research uses historical research methodology using primary sources from colonial archives in the form of besluit (decision letters), and secondary sources in the form of books and scientific journals. This research aims to see how the pattern of education in West Sumatra from the 14th Century to the 19th Century produced national movement figures. The results of this research found that the education pattern in West Sumatra society is divided into two, namely traditional education which has existed since pre-Islamic times and post-modern Islamization. Both modern education has existed since the arrival of colonial influence, which was marked by the establishment of volkschools in West Sumatra in the mid-19th century. All educational processes have their respective roles. Traditional education aims to prepare members of West Sumatra society to live based on existing customs. Meanwhile, post-Islamization education with the influence of Western nations aims to produce government employees.